Small-polaron hopping conductivity in the PrBa2Cu3-xGaxO7-y system - Triberis, G.P.; Guskos, N.; V. Likodimos (Physica C: Superconductivity and its applications, 1994)
Based on experimental observations we propose the small-polaron hopping model to interpret the behavior of the resistivity of PrBa2Cu3-xGaxO7-y system with x = 0.00-0.60 in a wide temperature range (14-290 K), reported by other workers. percolation arguments we evaluate the maximum hopping distances, at high and low temperatures, together with other relevant parameters, and we give a unified and meaningful explanation of the transport mechanism, for different Ga concentrations and the entire temperature range. © 1994.